Malachi: fidelity to the great king - Tucker, W. Dennis (Zondervan exegetical commentary on the Old Testament, 2024)
"The Zondervan Exegetical Commentary on the Old Testament series serves pastors and teachers by providing them with a careful discourse analysis and interpretation of the Hebrew text, tracing the flow of argument in each Old Testament book and showing that how a biblical author says something is just as important as what they say"--